2020
DOI: 10.18805/ijare.a-5397
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Novel Strain of Metarhizium anisopliae (Metarhizium anisopliae Strain DULS TTRA) against Odontotermes obesus, A Pest of Camellia sinensis (L.) O. Kuntze

Abstract: Odontotermes obesus (Rambur) is an important termite pest of tea of North East India. The current study shows that a novel strain of Metarhizium anisopliae (Metarhizium anisopliae strain DULS TTRA, Accession no. KT 119358) a tea soil fungus is highly pathogenic to both worker and soldier caste of Odontotermes obesus in in-vitro condition. Efficacy of the experimental fungi further assessed by comparing with commercial formulation showed to have less LT50 and LC50 than the established virulent strain. We recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Singha et al (2011) reported that the formulation of M. anisopliae s.l. (1 × 10 9 spores/ml) reduced termite populations up to 50% and Hazarika et al (2021), reported M. anisopliae s.l. (1 × 10 9 spores/ml) reduced termite populations up to 78% in different tea gardens in Assam states, India, however, in the present investigation more efficacy was reported, the concentration 1000 ml/ ha (2 × 10 7 conidial/ml) concentration was capable to reduce 70 to 85% populations of M. obesi.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Singha et al (2011) reported that the formulation of M. anisopliae s.l. (1 × 10 9 spores/ml) reduced termite populations up to 50% and Hazarika et al (2021), reported M. anisopliae s.l. (1 × 10 9 spores/ml) reduced termite populations up to 78% in different tea gardens in Assam states, India, however, in the present investigation more efficacy was reported, the concentration 1000 ml/ ha (2 × 10 7 conidial/ml) concentration was capable to reduce 70 to 85% populations of M. obesi.…”
Section: Discussionmentioning
confidence: 96%
“…During in vitro screening of M. anisopliae isolates against termite Singha et al (2011) reported 78-100% mortality after 8th day of application. Hazarika et al (2021), while studying on the bio-efficacy of M. anisopliae against termite reported that 1 × 10 9 conidia per ml concentrations of M. anisopliae could cause 92-100% mortality in both worker and soldier caste of termites. Field application of M. anisopliae (10 9 spores/ml) against termites damaging tea plants in Assam, India revealed that, the effectiveness was concentration dependent showing more effectiveness in reducing the insect populations than the lowest concentrations (Singha et al 2011).…”
Section: Discussionmentioning
confidence: 99%